Confidence and the financial accelerator - Christian Myohl; Yannic Stucki (University of Bern, Department of Economics, 2018)
We introduce financial frictions in the spirit of Bernanke, Gertler, and Gilchrist (1999) into a standard RBC model and use the heterogeneous-prior framework of Angeletos, Collard, and Dellas (2018) to accommodate confidence-driven business cycle fluctuations. We show that financial frictions strongly amplify the response to confidence shocks - more strongly than the response to fundamental shocks. Furthermore, we show that in the presence of financial frictions, prolonged episodes of unfounded optimism cause boom-bust cycles in investment and to a lesser extent in output. In particular, the financial state of the economy deteriorates severely after the initial boom, which leaves the economy more vulnerable to adverse shocks.
Keywords: E32; E44; 330; Confidence; sentiments; financial accelerator; financial frictions; higher-order beliefs; higher-order uncertainty; business cycle